(untitled) (Revista Rupturas, 2025)
This paper is only one part of the result of a comparative and qualitative social research project. This project studied the urban common wealth and the dynamics of urban socio-spatial segregation in two neighborhoods. The first, El Gran Tejarcillos, is located in Alajuelita, and the other, Bello Horizonte, is located in Escazú. This scientific article focuses on the inhabitants of El Gran Tejarcillos, who face a great diversity of problems such as: poverty, social inequality, an underground illegal drug market, social and territorial stigmas, social violence, family disintegration and so on and so forth. The main conclusion is that the neighbors along with their neighborhood organizations face all those problems alone because they have been suffering political instrumentalization and abandonment from the state for decades. The big picture at El Gran Tejarcillos shows us more a case of a common tragedy than a case a common wealth in the current neoliberal Costa Rican society.